EVALUASI PROGRAM PENDAMPINGAN KEPALA SEKOLAH OLEH PENGAWAS SEKOLAH BAGI PENINGKATAN KUALITAS PEMBELAJARAN DI PALANGKARAYA - Iin Nurbudiyani (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study aims to evaluation of training programs mentoring principals by school supervisors to improving the quality of learning in Palangkaraya. This study included evaluation using descriptive analytic method. Instrument data collection using questionnaires, tests, review of documents, and focus group discussion. This research target is 8 supervisors who each cultivate 3-5 schools that amounted to 35 schools. Evaluation model used in this study are four levels of Kirkpatrick, reaction, learning, behavior and results. Itis concluded that (1) This training has relevance level of 85.14% (good categories), (2) The training has the effectiveness rate of 92.57% (excellent categories), and the effect size of 2.0832 category great because of greater than 0.8, (3) training is a positive impact on: (a) implementation of the management of the school curriculum with an average score of 84.13 (good categories), (b) implementation of lesson preparation, implementation of learning and learning outcomes with an average score of 82.91 (good categories), so the overall impact with an average of 83.52 (good categories).